Application of Six Sigma methodology in an Indian chemical company. Issue 2 (14th April 2020) - Patyal, Vishal Singh; Modgil, Sachin; Koilakuntla, Maddulety
Abstract : Purpose: The aim of this paper is to deploy Six Sigma (SS) methodology for addressing the customer complaints pertaining to Chemical-X in an Indian chemical company. Design/methodology/approach: The study followed a structured Define, Measure, Analyze, Improve, Control (DMAIC) approach to address the customer complaints. The complaints have been classified into different categories along with a project charter in the define phase. In the measure phase, measurement system analysis (MSA) and supplier, input, process, output and control (SIPOC) have been applied. In the analyze and improve phase, why–why analysis, process capability study, how–how analysis, Gage repeatability and reproducibility and Taguchi design have been applied to optimize the manufacturing process parameters for Chemical-X. Lastly, in the control phase, validation of 20 batches has been piloted to validate the optimized parameters. Findings: The findings of this study highlight the optimization and prioritization of the process parameters. It shows that humidity has the least impact on the manufacturing of Chemical-X, whereas shift type has the maximum impact. The experimental output indicates that the 1st Shift, the holding time after grinding should be twenty-four hours, and the temperature after grinding should be 40 °C to reduce the customer complaints concerning lumps formation in Chemical-X. Research limitations/implications: The study is performed for a single product (Chemical-X). It has focused only from the manufacturing process view and not from the transportation, suppliers and downstream supply chain view. Originality/value: A systematic and data-driven approach of the SS methodology ensured that the customer complaints due to lumps formation reduced from 5% (approx.) to 1% (approx.) which resulted in the cost saving of INR 4 million (approx.) annually.